The School's role in achieving psychological Security for Primary School Students from the point of view of Parents - Najem Mahmoud, Khaled (Al-Adab Journal, 2021)
The study aimed to identify school's role in achieving psychological security among primary school students from the point of view parents to achieve this research, the researcher chose two schools from the Baquba schools at the center, the school has a role in achieving psychological security from students from the parent's point of view, and accordingly some recommendations and suggestions were made.